2021
DOI: 10.1111/birt.12591
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family physicians in rural maternity care

Abstract: Background Reduced access to maternity care in rural areas of the United States presents a significant burden to pregnant persons and infants. The objective of this study was to estimate the impact of family physicians (FPs) on access to maternity care in rural United States hospitals, especially where other providers may not be available. Methods We administered a survey to 216 rural hospitals in 10 US states inquiring about the number of babies delivered from 2013 to 2017, the types of delivering physicians,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In this study, an average of 63% of babies were delivered by Family Physicians in these hospitals. 23 Similarly, a 2021 study of 185 rural hospitals in the United States demonstrated that Family Physicians delivered babies in 67% of the hospitals. They were the only delivering physician in 27% of the hospitals overall and in 40% of the hospitals in which Family Physicians did deliveries.…”
Section: Intrapartum Care and Deliveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an average of 63% of babies were delivered by Family Physicians in these hospitals. 23 Similarly, a 2021 study of 185 rural hospitals in the United States demonstrated that Family Physicians delivered babies in 67% of the hospitals. They were the only delivering physician in 27% of the hospitals overall and in 40% of the hospitals in which Family Physicians did deliveries.…”
Section: Intrapartum Care and Deliveriesmentioning
confidence: 99%
“…22 Of rural hospitals that provide maternity care, 46% have Family Physicians that provide cesarean deliveries as the primary surgeon. 23 In addition, in 38.6% of rural counties, they are the only physician performing them. 4 This further highlights the need to support Family Physicians providing not only maternity care but having the proper training and skillset to provide operative care, in particular in rural environments.…”
Section: Several Studies Have Demonstrated the Safety Of Family Physi...mentioning
confidence: 99%
“…Family physicians are the most common health professional providing rural OB care, but the number of family physicians practicing OB is declining. [1][2][3][4] The United States is also experiencing a national shortage of obstetricians and gynecologists (Ob-Gyns), more acutely in rural areas. 1,4 In 2019, more than half of rural counties had no family physicians who delivered babies, and nearly one-third had no clinicians practicing OB.…”
Section: Introductionmentioning
confidence: 99%
“…Family physicians (FPs) play a significant role in improving perinatal health equity as they fill gaps in access to care in rural areas and among underserved populations, conducting seven percent of all deliveries (translating to approximately 280,000 deliveries per year) and an even greater percentage of prenatal and postpartum care 1 . FPs are distinctive in that they provide a comprehensive model of “dyad care,” providing longitudinal care for the family including reproductive and preconception care through postpartum, infant, and pediatric care 2–4 . Because FPs are trained in the biopsychosocial model to have a broad understanding of patients, families, and communities, and to understand multiple stressors placed on patients as seen in the COVID‐19 pandemic, they provide a unique perspective on the impact of the pandemic on the care of pregnant and postpartum patients 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…1 FPs are distinctive in that they provide a comprehensive model of "dyad care," providing longitudinal care for the family including reproductive and preconception care through postpartum, infant, and pediatric care. [2][3][4] Because FPs are trained in the biopsychosocial model to have a broad understanding of patients, families, and communities, and to understand multiple stressors placed on patients as seen in the COVID-19 pandemic, they provide a unique perspective on the impact of the pandemic on the care of pregnant and postpartum patients. 4,5 Clinics and hospitals have implemented new protocols and policies aimed at reducing the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%